بندا أتشيه MTsN Rukoh على ترقية مهارة القراءة عند الطلاب ب Problem Based Learning فعالية تطبيق - Muharram, Fivi; Idris, Aisyah; Ninoersy, Tarmizi (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2022)
The subject of this research is "The Effectiveness of Problem Based Learning on Promoting Students' Reading Skills at MTsN Rukoh Banda Aceh". One of the reasons that led the researcher to write this thesis is that some students during the process of teaching and learning are having trouble reading and can not read the correct reading and sound. Some characters do not match their output. The objectives of this thesis are to identify the effectiveness of Problem Based Learning in promoting students 'reading skills and to identify students' problem based learning activities on reading instruction. The research method used by the researcher in writing this thesis is empirical research. In the data collection, the researcher taught the Arabic language by direct testing and observation. The results of research obtained by the researcher in this thesis is that the application of Problem Based Learning is effective in promoting the reading skills of students. The difference between the control group and the experimental group is 11.962, and the result of student activities in Problem Based Learning is 89.70.